The Art of Eric Carle - Carle, Eric; Marcus, Leonard S., 1950- (New York : World of Eric Carle, an imprint of Penguin Random House LLC, 2021)
Portrait of the childrens author/illustrator, includes over sixty full-color illustrations from his books, examples of his student artwork, autobiographical information and photographs, and essays on his life and art by friends, critics, and colleagues.
"First published in 1996 by Philomel Books"--Title page verso.
Keywords: Carle, Eric -- Themes, motives; Young adult literature; Illustrators -- United States; Biography; Young adult literature; Illustration of books -- United States; 20th century; Young adult literature; Childrens literature -- Authorship; Young adult literature; Picture books for children -- United States; Young adult literature